PENGARUH KEMAMPUAN PENGELOLAAN TATA RUANG PEMUKIMAN BANTARAN SUNGAI DAN GENDER TERHADAP NEW INVIRONMENTAL PARADIGM (NEP) - Bahrawi Bahrawi; Diana Vivanti; Yusriani Sapta Dewi (Jurnal Green Growth dan Manajemen Lingkungan, 2017)
The objective of this research is to find out the effect of Capabilities OF Resilience management of river (CRMR) and gender (G) on new Environmental Paradigm (NEP). An expost facto method has been used by selecting 19 sample for each cell. Reliability of CRMR was .878, and New Environmental Paradigm (NEP) was .91. Data analyzed by two-way ANOVA. Research results revealed that there was new environmental paradigm significant difference between those people who have high capabilities of resilience management of river and low capabilities of resilience management of river . Moreover, there was significant interaction effect between Capabilities OF Resilience management of river (CRMR) and gender (G) on New Environmental paradigm (NEP)